2007
DOI: 10.1002/cne.21515
|View full text |Cite
|
Sign up to set email alerts
|

R6/2 neurons with intranuclear inclusions survive for prolonged periods in the brains of chimeric mice

Abstract: The R6/2 mouse possesses mutant exon 1 of human Hdh, and R6/2 mice with 150 CAG repeats show neurological abnormalities by 10 weeks and die by 15 weeks. Few brain abnormalities, however, are evident at death, other than widespread ubiquitinated neuronal intranuclear inclusions (NIIs). We constructed R6/2t+/t- <--> wildtype (WT) chimeric mice to prolong survival of R6/2 cells and determine if neuronal death and/or neuronal injury become evident with longer survival. ROSA26 mice (which bear a lacZ transgene) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 152 publications
(271 reference statements)
5
48
0
Order By: Relevance
“…Importantly, HD patients show high levels of astrogliosis 3 and this pathological hallmark also shows a progressive increase in all tested animal models of HD in correlation with the degenerative process. [31][32][33]53 Interestingly, our study results show that pGFAP-BDNF transgenic astrocytes release high levels of this neurotrophin only on stimulation. We did not find differences in BDNF release between pGFAP-BDNF astrocytes and wt astrocytes in basal conditions.…”
Section: Conditional Release Of Bdnf In Huntington's Disease a Giraltmentioning
confidence: 51%
“…Importantly, HD patients show high levels of astrogliosis 3 and this pathological hallmark also shows a progressive increase in all tested animal models of HD in correlation with the degenerative process. [31][32][33]53 Interestingly, our study results show that pGFAP-BDNF transgenic astrocytes release high levels of this neurotrophin only on stimulation. We did not find differences in BDNF release between pGFAP-BDNF astrocytes and wt astrocytes in basal conditions.…”
Section: Conditional Release Of Bdnf In Huntington's Disease a Giraltmentioning
confidence: 51%
“…The anti-D1 antibody was a rat monoclonal directed against the 97-amino acid C-terminal fragment of human D1 (Sigma-Aldrich, D187), whose specificity has been demonstrated previously (Levey et al, 1993; Hersch et al, 1995). The anti-ENK used was a rabbit polyclonal antibody against leucine-enkephalin (ImmunoStar, 20066) whose specificity has also been shown previously (Reiner, 1987; Reiner et al, 2007; Tripathi et al, 2010). Immunolabeling for DARPP32 was carried out using an anti-DARPP32 (generously provided by P. Greengard and H. Hemmings), whose specificity has been previously documented (Ouimet et al, 1984).…”
Section: Methodsmentioning
confidence: 93%
“…8). It has been suggested that the toxic influence of these inclusions leads to a differential loss of specific subsets of neurons; however, this is still a topic of debate as there is evidence for both deleterious and protective effects of huntingtin aggregation (Davies et al 1999;Arrasate et al 2004;Reiner et al 2007). The important steps of the aggregate toxicity hypothesis may involve proteolysis, nuclear translocation, and aggregation.…”
Section: Aggregatesmentioning
confidence: 99%